The Effect of Billboards Contents on Female Legislative Candidates’ Electability in the 2019 Legislative Election in Kendari City, Indonesia - Husain, Muhammad Najib; Zuada, La Husen; Kholil, H.M.; Noegroho, Agoeng; Abadi, Totok Wahyu (Journal of Ecohumanism, 2025)
Since the revision of the 2017 Election Law, the affirmation of women in electro- democracy in Indonesia has become important. The participation of women in the election of legislative candidates has increased. This article, mixed methods research, examines the use of billboards as a campaign medium for women candidates to explain how it impacts their electability. The results of the study found that female legislative candidates in Kendari City use billboards as a campaign medium to introduce themselves to a wide audience. As a campaign strategy to influence voters, the legislative candidates display interesting contents to gain voters' sympathy on their billboards. An interesting finding of this study is that content depicting ethnic identity significantly increases electability female legislative candidates The concept of ethnic identity used in this research is the selection of clan as one of the elements/features of ethnic identity. The author also recommends that female candidates who run for office by showing clan identity have a great chance of being elected in their area.